Anaesthetic Management during Balloon Atrial Septostomy in Transposition of Great Arteries - Devina Ravelia Tiffany Subroto; Ulya A'malia; Ardian Wibowo (Solo Journal of Anesthesi, Pain and Critical Care (SOJA), 2023)
Background: Transposition of the great arteries (TGA) is a congenital heart defect that can cause death in 30% of the first week of birth, 50% in the first month, 70% in 6 months, and 90% in the first year, thus requiring immediate corrective action in neonates with rapid early detection. The purpose of this case study is to highlight management considerations in TGA cases in the Balloon Atrial septostomy (BAS) procedure.Discussion: A 1-day-old newborn girl was brought to               Dr. Moewardi General Hospital in February 2022. The patient had a history of cyanosis when she cried and was born with an APGAR score of 6.7.8. The lips were cyanotic on physical examination, with a SpO2 of 77% with a nasal O2 of 2 lpm. The echocardiography results obtained TGA, ASD II, PFO, and PDA. The patient then underwent a BAS procedure. Anesthesia management was performed using ketamine for induction, air bar, O2, and sevoflurane for maintenance of anesthesia. The operation was successful, and postoperative care was carried out. Anesthesia management aims to keep SVR and PVR to a minimum, with a PVR lower than SVR, to prevent desaturation in the patient. A decrease in PVR also can increase pulmonary blood flow, allowing more blood to be mixed and higher oxygen saturation in the blood for the patient.Conclusion: The principle of anesthesia management in TGA cases is to avoid a reduction in cardiac output and SVR and keep the PVR lower than the SVR.